Economic analysis of ginger cultivation in selected locations of Nepal - Poudel, RR; Regmi, PP; Thapa, RB; Gc, YD; Kc, DB (Bangladesh Journal of Agricultural Research, 2018)
Although Ginger is the main cash crop for small farmers across the country, the economic condition is not satisfactory which can be attributed to high cost of product and low productivity. The study was conducted in four ginger growing areas of Palpa, Nepal in 2012, focusing on cost factors of various inputs. The study revealed that ginger production was profitable on cash cost basis (BCR 7.22). Seed have major cost share for ginger production (65.1%). The estimated coefficients of Cobb-Douglas production function showed that seed, labor and number of years for crop rotation were the significant factors for ginger production. The study concluded that ginger production can be made viable enterprise with increased focus on source seed production and distribution. Bangladesh J. Agril. Res. 42(4): 681-691, December 2017